2015
DOI: 10.1139/gen-2015-0090
|View full text |Cite
|
Sign up to set email alerts
|

Atypical mitochondrial inheritance patterns in eukaryotes

Abstract: Mitochondrial DNA (mtDNA) is predominantly maternally inherited in eukaryotes. Diverse molecular mechanisms underlying the phenomenon of strict maternal inheritance (SMI) of mtDNA have been described, but the evolutionary forces responsible for its predominance in eukaryotes remain to be elucidated. Exceptions to SMI have been reported in diverse eukaryotic taxa, leading to the prediction that several distinct molecular mechanisms controlling mtDNA transmission are present among the eukaryotes. We propose that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 76 publications
2
76
0
1
Order By: Relevance
“…One possibility is occasional inheritance of mitochondria and symbionts through the paternal germline (paternal leakage). Paternal leakage is a common phenomenon that occurs in a variety of different taxa at low frequency (reviewed in Breton & Stewart, ), which would agree with our observation that introgressed symbionts are rare. The second possibility is doubly uniparental inheritance (DUI) of mitochondria, which would involve a regulated system of paternal cotransmission as suggested previously for Vesicomya sp.…”
Section: Discussionsupporting
confidence: 92%
“…One possibility is occasional inheritance of mitochondria and symbionts through the paternal germline (paternal leakage). Paternal leakage is a common phenomenon that occurs in a variety of different taxa at low frequency (reviewed in Breton & Stewart, ), which would agree with our observation that introgressed symbionts are rare. The second possibility is doubly uniparental inheritance (DUI) of mitochondria, which would involve a regulated system of paternal cotransmission as suggested previously for Vesicomya sp.…”
Section: Discussionsupporting
confidence: 92%
“…It is the first reported species with DUI from the family Semelidae, raising the total number of veneroid families in which DUI has been discovered to six (Theologidis et al, 2008; Plazzi, 2015; Dégletagne, Abele & Held, 2016; present study). Apart from providing new insights into the taxonomic distribution of DUI, S. plana may play a key role for better understanding the hypothesized role of DUI in sex determination (e.g., Breton et al, 2007; Breton et al, 2011a; Breton et al, 2014; Breton & Stewart, 2015; Mitchell et al, 2016). Indeed, an “intersex” condition, i.e., the appearance of oocytes in male gonads following endocrine disruption, has been reported in S. plana and is associated with differentially expressed mitochondrial transcripts in males exhibiting intersex compared to “normal” males (Chesman & Langston, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Besides Metazoa, evidence also supports the existence of biparental inheritance of mitochondria in various plant and fungal taxa (see Barr et al. and Breton and Stewart for reviews). The discovery of DUI in bivalves dates back to 1990, when Fisher and Skibinski () observed that mitochondrial DNA (mtDNA) heteroplasmy was common in Mytilus Linnaeus, 1758 populations in Britain.…”
Section: Introductionmentioning
confidence: 89%